Pengembangan Modul Berbasis Inkuiri Terbimbing Bermuatan Artikel Ilmiah Populer Pada Materi Sistem Saraf Kelas XI - Rima Isnaini; Ayatussa'adah Ayatussa'adah (Jurnal Penelitian Sains dan Pendidikan (JPSP), 2021)
The purpose of this study is to find out the description, validity and practicality of guided inquiry-based modules containing popular scientific articles on nervous system. This type of research is Research and Development (R&D) with ADDIE development model consisting of 5 stages of development, namely Analysis, Design, Development, Implementation and Evaluation. Product testing is on a small scale at MA Darul Ulum Palangka Raya and the instrument used is a questionnaire validation of material experts and media experts to measure the validity and questionnaire responses of students and observations of the implementation to measure practicality. The results showed that the description of the module developed was in the form of a module whose base contained the stages of guided inquiry and was a module that met the material and media aspects and was in accordance with the ADDIE development stage. The module that was developed gained 87% material expert validation value with valid criteria and media expert validation obtained 75% percentage with sufficiently valid criteria and can be used at a later stage. While the practicality score obtained a percentage of 82% with very good criteria and the feasibility obtained a percentage of 97.22% with very successful criteria. Based on the results of the study, the guided inquiry-based module product containing popular scientific articles on the nervous system material was declared valid and practical on a small scale test at MA Darul Ulum Palangka Raya